Forgotten voices : the expulsion of the Germans from Eastern Europe after World War II - Merten, Ulrich (2012)
More than sixty years ago the German Nazi regime committed great crimes against innocent civilian victims: Jews, Poles, Russians, Serbs, and other people of Central and Eastern Europe. At war's end, however, innocent German civilians in turn became victims of crimes against humanity. Forgotten Voices lets these victims of ethnic cleansing tell their story in their own words, so that they and what they endured are not forgotten. This volume is an important supplement to the voices of victims of totalitarianism and has been written in order to keep the historical record clear.